Man-The-Shaman is it the Whole Story? A Feminist Perspective on the San Rock Art of Southern Africa - Stevenson, Judith S. (University of the Witwatersrand, Johannesburg, 1995)
Ethnographic accounts show that both shamanic and gender rituals play a critical role in San culture. Although 30% of the women and 50% of the men become shamans, the literature investigating San rock art frequently defines 'Man-the-Shaman' and minimizes the feasibility of female depictions of this important social role. Prior rock art research has tended to separate shamanic and gender processes to the impoverishment of both. This dissertation investigates the symbolic connections between these two social spheres, and argues that they are inseparable. Through this examination of gender and shamanic roles in San society this dissertation argues that metaphors reflect these two social spheres. It also argues that metaphors are a way of life which are expressed both in reality and non-reality. With these points in mind, it investigates the role of men and women as related to San rock art through social roles.
Keywords: Ethnographic; Man-the-Shaman; San rock art; Feminist Archaeology; Union Catalogue for Thesis and Dissertations (UCTD)